LINGUISTIC AND STYLISTIC FEATURES OF ENVIRONMENTAL SLOGANS (BASED ON THE ENGLISH LANGUAGE) - N.P. Merzlyakova; M.A.Karelina (Многоязычие в образовательном пространстве)
The aim of our research is to study the linguistic and stylistic features of ecological discourse by analysing English-language environmental slogans. The relevance of the study is conditioned by the fact that environmental slogans in English are widely spread in the international context and influence the formation of global ecological discourse. Representing a set of texts aimed at discussing environmental problems, the ecological discourse forms environmental awareness and mobilises society to solve environmental problems. The method of linguistic and contextual analysis allowed us to study the lexical specificity, syntactic structure, morphological features, stylistic and phonetic techniques of environmental slogans, which gives us the opportunity to better understand their impact on the addressee and helps to create new persuasive and inspiring messages for individual and collective action.